Association of wearable device-measured physical activity with full-course diabetic retinopathy and retinal traits: insights from the middle-aged and older adult cohort - Chenxiao Shen; Zijing Du; Chunran Lai; Ting Su; Qiaowei Wu; Yanlei Chen; Ying Fang; Zhuoting Zhu; Xiayin Zhang; Honghua Yu (Diabetology & Metabolic Syndrome)
Abstract Purpose To assess accelerometer-measured physical activity (PA) in patients with all stages of diabetic retinopathy (DR) and investigate its association with specific retinal structural metrics. Methods This extensive cohort study included 13,600 participants with an average age of 56.39 years. These subjects were divided into four groups: non-diabetes mellitus, prediabetes mellitus (Pre-DM), diabetes mellitus (DM) without DR, and DR. We evaluated multivariate-adjusted associations of PA with DR progression using logistic regression and with retinal sublayer thickness using hierarchical linear model (HLM). The mediating role of body mass index (BMI) was tested to investigate the true association between PA and the full spectrum DR. Results As DR progressed, the durations of moderate-intensity PA (MPA) and moderate-vigorous PA (MVPA) decreased significantly by 29% (odds ratio (OR) = 0.71, 95% CI = 0.57–0.90) to 78% (OR = 0.22, 95% CI = 0.14–0.35) and 21% (OR = 0.79, 95% CI = 0.71–0.89) to 55% (OR = 0.45, 95% CI = 0.30–0.67), respectively. Morning MPA and MVPA (6:00–12:00) were protective factors against DR, whereas late-night PA (0:00–5:59) heightened DR risk. The multivariate-adjusted linear interaction model revealed that the positive effect of MPA and MVPA on the thickness of ganglion cell-inner plexiform layer (GCIPL), macular thickness (MT), and inner nuclear layer-external limiting membrane was significantly associated with DR disease status (interaction P < 0.05). Higher MPA and MVPA were correlated with accelerated thickening rates of the GCIPL and MT sublayers, ranging from Pre-DM to those with established DR. 35.7% and 58.7% of the associations between MPA, MVPA, and the full spectrum DR were mediated by lower BMI, respectively. Conclusions The diminution of PA is associated with the progression of DR and the attenuation of retinal sublayer thickness, and our findings support current PA recommendations promoting interventions to decelerate DR progression and preserve retinal health.